PENGARUH KERJASAMA TIM DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAWN PADA PT. NIKOS DISTRIBUTION INDONESIA, CABANG DEPOK - Pandito, Riski Akbar; Syamsuddin, Rahmi Andini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of teamwork and the work environment on employee performance at PT. Nikos Distribution Indonesia, Depok Branch. The background of this research is based on findings of a decline in trust among employees and workplace noise, as well as suboptimal work quantity. This study uses a quantitative approach with an associative research design. The sample used was the entire population of 53 employees, using a saturated sampling technique. Data were collected through questionnaires and analyzed using simple and multiple linear regression, as well as t-tests and F-tests with SPSS version 27. The results show that the teamwork variable (X1) partially has a significant effect on employee performance (Y), with a t-count value of 8.583 > t-table 1.675 and a significance value of 0.001 < 0.05. Its contribution to employee performance is 59.1% (R² = 0.591). The work motivation variable (X2) also partially has a significant effect, with a t-count value of 13.211 > t-table 1.675 and a significance value of 0.001 < 0.05, and a contribution of 77.4% (R² = 0.774). Simultaneously, both variables X1 and X2 significantly influence employee performance, with an F-count value of 101.502 > F-table 3.183 and a significance value of 0.001 < 0.05. The simultaneous coefficient of determination is 80.2% (R² = 0.802), indicating that teamwork and the work environment together explain 80.2% of the variation in employee performance, while the remaining percentage is influenced by other factors. In conclusion, both teamwork and the work environment have a significant effect on employee performance, both partially and simultaneously. Therefore, improving trust among employees and paying attention to optimal workplace noise levels are very important in enhancing employee performance.